Qualitative analysis of cyber security vulnerability for Ethernet-based train communication network - YUE Chuan; WANG Lide; SHEN Ping; DUO Ruifeng; WANG Dengrui (机车电传动)
Interactions between the Ethernet-based train communication network (ETCN) and the outside information environment are increasing rapidly, which means that ETCN is facing severe cyber security threats. There is no systematic and macroscopic qualitative analysis of the vulnerability of ETCN at home and abroad, therefore it is urgent to analyze its security vulnerability. Firstly, from the perspective of network protocols and network devices, a macroscopic qualitative analysis of the vulnerabilities of ETCN were carried out. Secondly, potential attacks against ETCN were analyzed through the subjects, routes, and behaviors of attacks. At last, an ETCN attack testbed was built to conduct experiments on several kinds of primary attacks. Experimental results indicate that the vulnerabilities exploited by these attacks exist in ETCN and are easy to be compromised.